Effect of Storage Conditions and Antioxidants on the Oxidative Stability of Sunflower–Chia Oil Blends - Guiotto, Estefania Nancy (2014)
The mixture of different proportions of sunflower with chia oil provides a simple method to prepare edible oils with a wide range of desired fatty acid compositions. Sunflower–chia (90:10 and 80:20 wt/wt) oil blends with the addition of rosemary (ROS), ascorbyl palmitate (AP) and their blends (AP:ROS) were formulated to evaluate the oxidative stability during storage at two temperature levels normally used, cool (4 ± 1 °C) and room temperature (20 ± 2 °C) for a period of 360 days. Peroxide values (PV) of the oil blends with antioxidants stored at 4 ± 1 °C showed levels ≤10.0 mequiv O2/kg oil; the lowest levels of PV were found for blends with AP:ROS. Values higher than 10.0 mequiv O2/kg were observed between 120–240 days for oil blends stored at 20 ± 2 °C. Similar trends were observed with p-anisidine and Totox values. The oxidative stability determined by the Rancimat method and differential scanning calorimetry showed a greater susceptibility of the oils to oxidative deterioration with increasing unsaturated fatty acids content. The addition of antioxidants increased the induction time and decreased the Arrhenius rate constant, indicating an improvement in the oxidative stability for all the oil blends. Temperature had a strong influence on the stability of these blends during storage.